Gradual deterioration of fatty liver disease to liver cancer via inhibition of AMPK signaling pathways involved in energy-dependent disorders, cellular aging, and chronic inflammation - Meng, Sha-Sha; Gu, Hong-Wei; Zhang, Ting; Li, Yu-Sang; Tang, He-Bin (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Current studies suggest that fatty liver increases the chance of hepatocellular carcinoma. However, AMPK signaling pathway plays an important role. Moreover, 5’-AMP-activated protein kinase (AMPK) is closely associated with changes in the tumor microenvironment, such as inflammation, hypoxia, and aging. The aim of this study is to investigate the effect of the AMPK signaling pathway on the progression of fatty liver to HCC. In this paper, we used high-fat and nano-nitrosamines (nano-DEN) to establish a mouse liver cancer model. And we used transcriptomic approach to detect all mRNAs recorded in mouse liver samples at the 25th week. Liver cancer tissues microarrays from mice and humans were examined by immunohistochemical staining for the expression of proteins associated with the LKB1-AMPK-mTOR signaling pathway, inflammation, aging, and hypoxia. These included p-AMPK, LKB1, mTOR, COX-2, β-catenin, HMGB1, p16, and HIF-1α. Data were then collected at different times in the liver as well as in cancerous and paracancerous regions and analyzed by a multispectral imaging system. The results showed that most of the genes in the AMPK signaling pathway were downregulated in expression. Prakk1 expression was upregulated compared to control group, but downregulated in the cancerous regions compared to the paracancerous regions. Stk11 expression was downregulated in the cancerous regions. Mtor expression was upregulated in the cancerous regions. During liver cancer formation, deletion of LKB1 in the LKB1-AMPK-mTOR signaling pathway reduces phosphorylation of AMPK. It contributed to the upregulation of mTOR, which further led to the upregulation of HIF1α. In addition, the expression of β-catenin, COX-2 and HMGB1 was upregulated, as well as the expression of p16 was downregulated. These findings suggest that changes in the AMPK signaling pathway exacerbate the deterioration of disrupted energy metabolism, chronic inflammation, hypoxia, and cellular aging in the tumor microenvironment, promoting the development of fatty liver into liver cancer.